ANALISIS KEBIJAKAN EKONOMI DAN POLITIK INDUSTRI EKSPOR MINYAK KELAPA DI INDONESIA - Khoirunnisa, Khoirunnisa; Fridayani , Helen Dian; Atmojo, Muhammad Eko (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
The palm oil industry is a strategic sector in the Indonesian economy that plays a major role in foreign exchange earnings, job creation, and rural development. This study aims to analyze the impact of economic and political policies on the performance of Indonesia's palm oil export industry, focusing on the dynamics of regulation, incentives, exchange rates, as well as diplomatic relations and political stability. The method used is descriptive-analytical qualitative with a literature review approach and content analysis of various policy documents, scientific publications, and national statistical data. The results of the study indicate that export quota policies, fiscal incentives, and bilateral/multilateral trade agreements have a significant impact on the volume of exports and the competitiveness of Indonesian palm oil. Domestic political stability and international relations also determine the success of policies and the attractiveness of foreign investment. Considering environmental pressures and global sustainability demands, this study recommends the formulation of export policies that strike a better balance between economic growth, social justice, and environmental sustainability.